Ultrastructural characteristics of non-matured and in vitro matured oocytes collected from pre-pubertal and adult domestic cat ovaries - Martins, L. R.; Fernandes, C. B.; Minto, B. W.; Landim-Alvarenga, F. C.; Lopes, M. D. (Wiley, 2009)
The present study describes the ultrastructural characteristics of cat oocytes before maturation and after 12- and 24-h in vitro maturation (IVM). Oocytes were recovered from pre-pubertal and adult queen ovaries after ovariohysterectomy and a proportion were stored in glutaraldehyde at 4°C until examination by transmission electronic microscopy (TEM). Those selected for maturation were cultured before TEM in DMEM for 12 and 24 h at 38°C in a humidified environment of 5% O2, 5% CO2 and 90% N 2. Specimens were divided into six groups: non-matured oocytes from pre-pubertal queens (PP0), non-matured oocytes from adult queens (A0), 12-h in vitro matured oocytes from pre-pubertal queens (PP12), 12-h in vitro matured oocytes from adult queens (A12), 24-h in vitro matured oocytes from pre-pubertal queens (PP24) and 24-h in vitro matured oocytes from adult queens (A24). Across the treatment groups, it was possible to observe differences in the thickness of the perivitelline space, the penetration of cumulus cell projections forming a junctional complex, distribution and density of small vesicles, lipid droplets, microvilli, mitochondria and cortical granules and variable degrees of development of Golgi complexes. These findings demonstrated that ultrastructural analysis of oocytes matured in vitro is a valuable tool to evaluate oocyte cytoplasmic maturation and that this IVM protocol was efficient in inducing gradual morphological changes necessary for cytoplasmic maturation of pre-pubertal and adult cat oocytes. © 2009 Blackwell Verlag GmbH.